2017
DOI: 10.1007/s11274-017-2318-2
|View full text |Cite
|
Sign up to set email alerts
|

Microbial biodiversity of meadows under different modes of land use: catabolic and genetic fingerprinting

Abstract: The main goal of the study was to find differences in the bacterial community structure resulting from different ways of meadow management in order to get the first insight into microbial biodiversity in meadow samples. The next generation sequencing technique (454-pyrosequencing) was accompanied with the community level physiological profiling (CLPP) method in order to acquire combined knowledge of both genetic and catabolic bacterial fingerprinting of two studied meadows (hayland and pasture). Soil samples (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 49 publications
0
17
1
Order By: Relevance
“…Although the Fluvisols examined are also classified as sand loam due to their textural composition, the soils differ in physical-chemical parameters. The Gleysol analysed by Wolińska et al [51] was more acidic (pH~5.9) than that analysed here. Literature reports indicate that soil microbiomes may be dependent on both soil type and pH [6,[56][57][58].…”
Section: Microbial Metabolic Potential and Bacterial Community Composcontrasting
confidence: 59%
See 2 more Smart Citations
“…Although the Fluvisols examined are also classified as sand loam due to their textural composition, the soils differ in physical-chemical parameters. The Gleysol analysed by Wolińska et al [51] was more acidic (pH~5.9) than that analysed here. Literature reports indicate that soil microbiomes may be dependent on both soil type and pH [6,[56][57][58].…”
Section: Microbial Metabolic Potential and Bacterial Community Composcontrasting
confidence: 59%
“…Actinobacteria (average 60.56%) proved to be the dominant bacterial phylum in the three analysed Fluvisols, followed by Proteobacteria (average 21.85%). In the study of meadows located on Gleysol, the dominant phylum was Proteobacteria, while Actinobacteria occurred in a much lower amount (third place among the dominant phyla; less than 10% abundance) [51]. Although the Fluvisols examined are also classified as sand loam due to their textural composition, the soils differ in physical-chemical parameters.…”
Section: Microbial Metabolic Potential and Bacterial Community Composmentioning
confidence: 95%
See 1 more Smart Citation
“…By excluding the changing climatic conditions, locations, and agrotechnical treatments, the study focused on comparing the catabolic potential of microorganisms in different soil types. This is important because in research work it has been stated that the microbiological activity of soils is mainly influenced by applied agricultural management and fertilization [49][50][51]. Research by Jesus et al [52] showed that the type of plant community was a more important driver of soil microbial activity than the soil type.…”
Section: Discussionmentioning
confidence: 99%
“…Interpretation of the CLPPs was based on metabolic profiles obtained using Biolog ® ECO plates designed by Insam (1997) for the bacterial community, Biolog ® FF plates for aerobic fungal community, and Biolog ® AN plates for the anaerobic microbial community. The recent study of Borowik et al (2017) or Wolińska et al (2017) shows that the Biolog ® system is an useful tool to explore the shifts in microbial community functional diversity of different environments. One gram portions of biowaste/ biogas residues were shaken in 99 ml of sterile peptone water for 20 min at 20 °C and followed by incubation at 4 °C for 30 min.…”
Section: Community-level Physiological Profiling (Clpp) Analysismentioning
confidence: 99%